If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6w + -5 = 0 Reorder the terms: -5 + 6w = 0 Solving -5 + 6w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 6w = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 6w = 0 + 5 6w = 0 + 5 Combine like terms: 0 + 5 = 5 6w = 5 Divide each side by '6'. w = 0.8333333333 Simplifying w = 0.8333333333
| 6w-5= | | 6w-5= | | 6w-5= | | 6w-5= | | 6w-5= | | x=56-3x | | 6w-5= | | 0.4x=2.40 | | 2(4y-4)-6=17+y | | 3t+4+t=6 | | 2(4y-4)-6=17+y | | 6w-5= | | 25-2x=-(-6+7) | | 25-2x=-(-6+7) | | 6w-5= | | -2/3[24t-27]=-8[-t-4]-6 | | M/5/6=24 | | 9asd+10=21asd | | 3(k-8)-1(k+5)=23 | | 9asd+10=21asd | | 8m-15=77-3m | | 4x++12-4+2x= | | (5u+8)(6-u)=0 | | -57=6x+x-1 | | 4(.50+.75y)+3y=4 | | h(t)=-16t^2+72t+24 | | 5y-3(y-1)=4y+2 | | 7x+11x-8+x+12=180 | | -x+4-x+6=4 | | -4m+3=24 | | 6=(-3x)+6 | | 66=6(8x-4)-6(x+6) |